Pigmentary Changes in Systemic Sclerosis are Associated with More Severe Cutaneous Sclerosis and Severity of Other Systems: A Cross-sectional Study from India - Setu Mittal; Binod K. Khaitan; M. Ramam; Neena Khanna; Rahul Mahajan; Ashu Seith Bhalla; Manoj K. Singh; V. Sreenivas (Wolters Kluwer Medknow Publications, 2024)
Background: Pigmentary changes of the skin in systemic sclerosis in the form of diffuse hyperpigmentation and salt-and-pepper pigmentation are well documented in the literature; however, its association with disease severity and extent of underlying internal organ involvement has not been well studied. Aims: To assess the correlation between morphology and extent of pigmentary changes with the degree of cutaneous sclerosis and frequency and degree of major organ involvement. Methods: This was a cross-sectional descriptive study conducted in a tertiary care teaching hospital from December 2014 to November 2016. Consecutive patients of systemic sclerosis attending the outpatient department were screened, and patients satisfying the diagnosis as per the American Rheumatism Association criteria were recruited. Skin sclerosis was quantified using modified Rodnan skin score (MRSS), whereas pigmentary changes were calculated in terms of percentage of body surface area involved by rule-of-nine method. Investigations were carried out depending on organ involvement and as per respective specialty consultations with focus on pulmonary, cardiac, and gastrointestinal systems. Results: Of the 50 patients recruited, all had cutaneous involvement in the form of binding down of skin, followed by pigmentary changes. MRSS was significantly higher in patients with any pigmentary alteration (P = 0.03) compared to those without any pigmentary changes. There was a rising trend in between the MRSS severity and the proportion of patients with hyperpigmentation, and it was statistically significant (P = 0.04). Among systemic involvement, lung was involved in the form of interstitial lung disease in 94% patients (n = 47). However, skin pigmentation of any type was associated with lower high-resolution computed tomography scores (P = 0.02). Conclusion: This study shows that in systemic sclerosis patients presenting with pigmentary skin manifestations, cutaneous sclerosis is significantly higher.